(Retracted) The Representation of Rural Christianity in the Films of Gan Xiao’er - Li, Jing (Journal for Religion, Film and Media, 2023)
The religious dimension of Chinese cinema is, it has been observed, a “triple lacuna”in contemporary scholarship: in research on religion in China, in research on Chinesecinema, and in interdisciplinary research on film and religion. From 2002 to 2012, independentfilmmaker Gan Xiao’er directed three low-budget features that portrayedrural Christianity in China, a subject almost entirely absent from both Chinese mainstreammedia and independent films. In this article, I analyze Gan’s films by locatingthem in their social, political, and religious contexts, by comparing them with otherChinese films, and by linking them to the tradition of Western films that portray spirituality.I observe a progression in themes and style from Gan’s first feature, 山清水秀(The Only Sons, CN 2002), to his third, 在期待之中 (Waiting for God, CN 2012). I seekto show that Gan developed a restrained directorial style in order to connect withthe spirituality of Chinese peasants. Although he had to grope in the dark on manyaspects, his engagement with Christian themes has greatly expanded the narrativespace of Chinese cinema.